Implementation barriers and facilitators of Moyo foetal heart rate monitor during labour in public hospitals in Nepal - Ashish KC; Mikaela Rönnbäck; Urja Humgain; Omkar Basnet; Pratiksha Bhattarai; Anna Axelin (Global Health Action)
Background Globally, every year, approximately 1 million foetal deaths take place during the intrapartum period, fetal heart monitoring (FHRM) and timely intervention can reduce these deaths. Objective This study evaluates the implementation barriers and facilitators of a device, Moyo for FHRM. Methods The study adopted a qualitative study design in four hospitals in Nepal where Moyo was implemented for HRM. The study participants were labour room nurses and convenience sampling was used to select them. A total of 20 interviews were done to reach the data saturation. The interview transcripts were translated to English, and qualitative content analysis using deductive approach was applied. Results Using the deductive approach, the data were organised into three categories i) changes in practice of FHRM, ii) barriers to implementing Moyo and iii) facilitators of implementing Moyo. Moyo improved adherence to intermittent FHRM as the device could handle higher caseloads compared to the previous devices. The implementation of Moyo was hindered by difficulty to organise training ondevice during non-working hours, technical issue of the device, nurse mistrust towards the device and previous experience of poor implementation to similar innovations. Facilitators for implementation included effective training on how to use Moyo, improvement in intrapartum foetal monitoring and improvement in staff morale, ease of using the device, Plan Do Study Act (PDSA) meetings to improve use of Moyo and supportive leadership. Conclusion The change in FHRM practice suggests that the implementation of innovative solution such as Moyo was successful with adequate facilitation, supportive staff attitude and leadership.